2013
DOI: 10.1016/j.polymdegradstab.2013.05.017
|View full text |Cite
|
Sign up to set email alerts
|

The impact of volatile compounds released by paper on cellulose degradation in ambient hygrothermal conditions

Abstract: International audienceThe reactivity towards cellulose of various volatile compounds commonly released by paper was studied. Sheets of Whatman No. 1 (W1) and No. 40 (W40) were exposed to various concentrations of these compounds in vapour phase ranging from 20 to 80 ppm in closed vessels for 52 days in controlled ambient conditions, after which they were hygrothermally aged. The measured properties of the paper were copper number, degree of polymerization, zero-span breaking length, pH and yellowness index. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 51 publications
1
36
0
1
Order By: Relevance
“…They were initially proposed by Evan et al [32] and have largely been used in the cellulose chemistry community for the cellulose/CED system. They lead to DP v values that are (i) experimentally consistent with M w values determined by size exclusion chromatography and (ii) proportional to average number of monomer per macromolecule (DP) with a proportionality factor that is relatively close to 1 [33]. Eq.…”
Section: Degree Of Polymerizationsupporting
confidence: 65%
“…They were initially proposed by Evan et al [32] and have largely been used in the cellulose chemistry community for the cellulose/CED system. They lead to DP v values that are (i) experimentally consistent with M w values determined by size exclusion chromatography and (ii) proportional to average number of monomer per macromolecule (DP) with a proportionality factor that is relatively close to 1 [33]. Eq.…”
Section: Degree Of Polymerizationsupporting
confidence: 65%
“…(Area and Cheradame 2011;Ding and Wang 2007;Forsskåhl 2000: Hotle et al 2008Kaminska et al 2001;Kato and Cameron 1999;Malešič et al 2005;Porck 2000;Rasch and Scribner 1933;Reilly et al 2001;Shahani et al 2001;Strlič et al 2011;Tétreault et al 2013;Zou et al 1996a;Calvini 2014) Since the process of natural aging is too slow, the aging of cellulose has to be accelerated by elevating the temperature to be able to then extrapolate the rate of cellulose scission to room temperature conditions. For this prediction, the rate of degradation at different temperatures is measured and an Arrhenius plot is constructed.…”
Section: Introductionmentioning
confidence: 99%
“…Acetic acid and nitrogen dioxide were selected as the most harmful pollutants based on previous work by the authors (Menart et al 2011a(Menart et al , 2011b, and recent monitoring at the National Archives (UK) (Fenech et al 2010). Although formic acid has recently been proposed as a potential threat to paper (Tétreault et al 2013) it has not been selected for this study, as it is found in concentrations significantly lower compared to acetic acid (at least an order of magnitude) even in archival boxes.…”
Section: Methodsmentioning
confidence: 99%